METAFORA DALAM KOMENTAR BERITA GOSIP OMG - NFN Riani (Balai Bahasa Sulawesi Tengah, 2013)
The research relating on the use of metaphor is abundant because the metaphor has significant role in communication. Some of reseaches are Suprajaheni (2011), Aisah (2007), Efendi (2012), and Udu (2006). However, the research on the use of methafor in reader’s comment on Oh My God as part of yahoonews.com has not yet investigated. The method used in the research is qualitative descriptive as the purpose of the research is to discover and illustrate on how the form, the meaning, nd the fuction of metaphor used in reader’s comment. The result of research reveals that there are hree forms of metaphor, namely onthological thinking and autropomorphic, onthological thinking nd animalization, and onthological thinking and concrete into abstract. Meanwhile, from its fuction, metaphor is used to express commentator’s feeling, thinking, and emotion. In broad sense, the use of metaphor in OMG is a reflection of the commentator’s way of life in viewing his/her world.